Islamic Motifs in the Manuscripts of Lithuanian Tatars - Мишкинене, Галина (Acta Orientalia Vilnensia, 2002)
Being based on the analysis of three manuscripts dating back to the 18th century, the article examines peculiarities and modifications of Islamic doctrine. The manuscripts represent major kinds of literary works by the Muslims of the Grand Duchy of Lithuania. Three fundamental themes have been distinguished in each manuscript: a) religious (fragments from the Koran, prayers, explanations dealing with the Islamic doctrine); b) ritual (name-giving, burying, fasting); c) moral (didactic narratives, dialogues between prophets and God, moralizations). The focus is, indeed, on the Koranic doctrine of Islam that governs the narration and represents a binding link between narratives and moralizations.